Analysis of the Potential of Mossak Batak as a Tourist Attraction in Toba Regency - Ryos Gardio; Bambang TJ Hutagalung; Mery Silalahi; Ade Putera Arif Panjaitan; Rusmauli Simbolon (An International Journal Tourism and Community Review, 2025)
Mossak Batak Toba is a traditional martial art originating from the Batak Toba ethnic group in North Sumatra, passed down through generations. Characterized by swift, agile, and powerful movements, Mossak is not only a physical discipline but also embodies spiritual values such as courage, discipline, and loyalty. This study aims to identify and analyze the potential of Mossak Batak as a tourist attraction in Toba Regency from cultural, economic, and social perspectives, and to formulate strategies for optimizing its potential amid various existing challenges. This research employs a descriptive qualitative method, utilizing observation, interviews, and documentation as data collection techniques, with descriptive analysis and SWOT analysis as analytical tools. The findings reveal that Mossak Batak holds significant cultural value as an intangible heritage, economic potential through performances and cultural tourism training, and a social role in reinforcing local identity and pride. However, challenges such as limited digital promotion, the absence of educational materials, weak stakeholder coordination, and low community participation remain. The study concludes that with proper strategies—such as cross-sector collaboration, effective digital promotion, and the development of local cultural festivals—Mossak Batak can be elevated as a prominent tourist attraction in Toba Regency. This not only contributes to cultural preservation but also supports local economic growth and strengthens the global recognition of Batak cultural identity.